High-hardness molybdenum alloy and preparation method thereof

By adding CR elements to traditional TZM alloys and adopting SPS sintering technology, it prepares high -hard molybdenum alloy with significantly improved hardness, solve the problem of insufficient traditional TZM alloy hardness, and achieve higher hardness and easier preparation technology.

CN119368749APending Publication Date: 2025-01-28HENAN UNIV OF SCI & TECH
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411502720.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

The hardness of traditional TZM alloys is usually less than 250HV, making it difficult to resist severe wear of abrasive particles, affecting the service life of the mold and punch.

Method used

Add 6%-12%of CR elements on the basis of traditional TZM alloys. By discharged plasma sintering (SPS sintering), CR element is soluble in the molybdenum base, and a high-hard molybdenum alloy with a density of more than 98.2%.

Benefits of technology

A significant improvement of the hardness of the molybdenum alloy, the hardness can reach 409.4HV-557.2HV, which is significantly higher than the hardness of the molybdenum alloy reported by the current literature. Molybdenum alloy.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119368749A_ABST
    Figure CN119368749A_ABST
Patent Text Reader

Abstract

The invention relates to a high-hardness molybdenum alloy and a preparation method thereof.The molybdenum alloy comprises the main element chemical components of, by weight, 6%-12% of Cr, 0.4%-0.6% of Ti, 0.08%-0.1% of Zr, 0.06%-0.07% of C and the balance Mo and other inevitable impurities, spark plasma sintering is adopted for sintering preparation, and the specific process includes the steps that chromium powder, titanium hydride powder, zirconium hydride powder, carbon powder and molybdenum powder are mixed to obtain alloy powder, and the alloy powder is subjected to heat treatment to obtain the high-hardness molybdenum alloy. The method comprises the following steps: weighing a proper amount of powder, loading the powder into a graphite mold, wrapping a graphite felt, pre-pressing and forming, putting the graphite mold into spark plasma sintering equipment, vacuumizing, applying a certain pressure under a vacuum condition, and sintering at a specific temperature to prepare the high-hardness molybdenum alloy. The microhardness of the prepared high-hardness molybdenum alloy can reach 557.2 HV and is far higher than that of a traditional molybdenum alloy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of powder metallurgy, in particular to a high-hardness molybdenum alloy and a preparation method thereof. Background Art

[0002] TZM alloy is a molybdenum-based alloy containing titanium (Ti), zirconium (Zr) and carbon (C). TiC and ZrC are formed at the molybdenum grain boundaries to prevent grain growth. The performance of the molybdenum alloy is enhanced through solid solution strengthening and second phase strengthening mechanisms, resulting in good strength. Due to the formation of these high-hardness carbides, the hardness of the TZM alloy is higher than that of pure Mo. High-hardness TZM alloys are used to manufacture molds and punches, and can resist deformation or wear of mold materials during sintering and removing ceramic materials from the mold. However, the hardness of traditional TZM alloys is usually less than 250HV, and it is difficult to resist severe abrasive wear during use, which affects the service life of molds and punches. Therefore, the development of high-hardness molybdenum alloys is of great significance in the field of modern manufacturing. Summary of the invention

[0003] In order to solve the above problems, the purpose of the present invention is to provide a powder metallurgy high-hardness molybdenum alloy and a preparation method thereof, which has the characteristics of fast heating speed, short sintering time, fine grains of the prepared alloy and uniform composition. On the basis of the traditional TZM alloy, the Cr element is added, and through systematic research, the chemical composition of the new high-hardness molybdenum alloy is obtained. Through spark plasma sintering (SPS sintering), the Cr element is dissolved in the molybdenum matrix to prepare a high-hardness molybdenum alloy with a density of more than 98.2%.

[0004] The present invention provides a method for preparing a high-hardness molybdenum alloy, which specifically comprises the following steps:

[0005] (1) Mo, TiH2, ZrH2, C and Cr powders are used as raw materials, mixed and ball-milled in a certain ratio to obtain a uniformly mixed molybdenum alloy powder.

[0006] Furthermore, the ball milling in step (1) is performed by mixing the powder in a planetary ball mill for 60 hours;

[0007] Furthermore, the content of each component in the raw material in step (1) is calculated as follows in mass percentage: Cr powder: 6-12%, TiH2 powder: 0.4-0.6%, ZrH2 powder: 0.08-0.1%, C powder: 0.06-0.07%, and the remainder is molybdenum powder, wherein the total mass percentage of the content of each component of the raw material powder is 100%.

[0008] (2) Place the molybdenum alloy powder obtained in step (1) into a graphite mold, and cover the outside of the graphite mold with graphite felt.

[0009] Furthermore, in step (2), because of the high temperature sintering, the outside of the graphite mold is covered with graphite felt to prevent heat loss.

[0010] Furthermore, in step (2), the graphite mold is a circular graphite mold with a diameter of 30 mm.

[0011] (3) placing the graphite mold containing molybdenum alloy powder in step (2) into the SPS furnace chamber and pre-loading the mold;

[0012] Furthermore, in step (3), the graphite mold filled with molybdenum alloy powder in step (2) is placed in the SPS furnace chamber, the hydraulic system is started, the pressure head is manually controlled to descend, and the mold is pre-loaded, the pre-loading pressure is 10Mpa, and the time is 10-20s.

[0013] (4) placing the graphite mold obtained after pre-loading in step (3) into an SPS sintering furnace for sintering, and obtaining a high-hardness molybdenum alloy after sintering.

[0014] Furthermore, in step (4), the center of the graphite mold after pre-compression loading in step (3) is aligned with the infrared temperature measuring hole of the SPS sintering furnace, the furnace door is closed, a pressure of 40 MPa is applied to the graphite mold, and the furnace chamber is evacuated to 10 -2 Pa, and then sintering.

[0015] Furthermore, in step (4), the center of the graphite mold after pre-compression loading in step (3) is aligned with the infrared temperature measuring hole of the SPS sintering furnace, the furnace door is closed, a pressure of 40 MPa is applied to the graphite mold, and the furnace chamber is evacuated to 10 -2 Pa, and then sintering is carried out. The sintering process is specifically as follows: first, the temperature is heated from room temperature to 600°C within 5 minutes; secondly, it is heated from 600°C to 1700°C at a heating rate of 100°C / min, and finally it is heated from 1700°C to 1800°C at a heating rate of 50°C / min, and is kept at 1800°C for 20 minutes. After the insulation is completed, it is naturally cooled to 40°C to obtain a molybdenum alloy.

[0016] The present invention also provides a molybdenum alloy obtained according to the above preparation method.

[0017] Furthermore, the hardness of the molybdenum alloy is 409.4HV-557.2HV, and the density is above 98.06%.

[0018] Furthermore, the main chemical composition (wt%) of the molybdenum alloy is: Cr: 6-12%, Ti: 0.4-0.6%, Zr: 0.08-0.1%, C: 0.06-0.07%, and the remainder is Mo and other inevitable impurities.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] The present invention provides a high-hardness molybdenum alloy and a preparation method thereof. A high-hardness molybdenum alloy is prepared by adding 6%-12% by mass of Cr to traditional TZM. Compared with pure TZM alloy, Cr can be completely dissolved in the molybdenum matrix through SPS sintering, which greatly improves the hardness of the molybdenum alloy, and does not require additional processing steps. The process is simple and more conducive to rapid production. In addition, the preparation method reduces the sintering temperature and shortens the holding time. The applied load can more effectively discharge isolated pores in the material, inhibit grain growth, and prepare a high-hardness molybdenum alloy with fine grains and uniform structure. The hardness of the molybdenum alloy prepared by the present invention can reach 409.4HV-557.2HV, which is significantly higher than the molybdenum alloys currently reported in the literature. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 are scanning electron microscope photos of the microstructures of the molybdenum alloys prepared in Example 1, Example 2 and Example 3; DETAILED DESCRIPTION

[0022] In order to better understand the content of the present invention, the present invention will be further described below in conjunction with specific embodiments and drawings. The following embodiments are implemented based on the technology of the present invention, and detailed implementation methods and operating steps are given, but the protection scope of the present invention is not limited to the following embodiments.

[0023] Embodiment 1:

[0024] (1) Mo, TiH2, ZrH2, C, and Cr powders are used as raw materials, and the content of each component in the raw materials is calculated by mass percentage as follows: TiH2: 0.55%, ZrH2: 0.1%, C: 0.07%, Cr: 6.0%, and the remainder is molybdenum powder, wherein the total mass percentage of the content of each component of the raw material powder is 100%, and the raw material powders with the proportions are mixed and ball-milled, wherein the ball milling is performed by mixing the powders in a ball mill for 60 hours to obtain a mixed molybdenum alloy powder;

[0025] (2) placing the molybdenum alloy powder obtained in step (1) into a circular graphite mold with a diameter of 30 mm, and covering the outside of the graphite mold with graphite felt to prevent heat loss;

[0026] (3) placing the graphite mold containing molybdenum alloy powder in step (2) into the SPS furnace chamber, starting the hydraulic system, manually controlling the pressure head to descend, and pre-loading the mold, wherein the pre-loading pressure is 10 MPa and the time is 15 s;

[0027] (4) Align the center of the graphite mold after pre-loading in step (3) with the infrared temperature measuring hole of the SPS sintering furnace, close the furnace door, apply a pressure of 40 MPa to the graphite mold, and evacuate the furnace chamber to 10 -2 Pa, and then sintering is carried out. The sintering process is specifically as follows: first, the temperature is heated from room temperature to 600°C within 5 minutes; secondly, it is heated from 600°C to 1700°C at a heating rate of 100°C / min, and finally it is heated from 1700°C to 1800°C at a heating rate of 50°C / min, and is kept at 1800°C for 20 minutes. After the insulation is completed, it is naturally cooled to 40°C to obtain a molybdenum alloy.

[0028] The microstructure scanning electron microscope photos of the molybdenum alloy samples are shown in Figure 1 As shown in the middle figure (a), it can be seen that the alloy sample has uniform structure, fine grains and no obvious pores.

[0029] After testing, the hardness of the molybdenum alloy sample is 409.4HV and the density is 98.06%.

[0030] Embodiment 2:

[0031] (1) Mo, TiH2, ZrH2, C, and Cr powders are used as raw materials, and the content of each component in the raw materials is calculated by mass percentage as follows: TiH2: 0.5%, ZrH2: 0.08%, C: 0.06%, Cr: 9.0%, and the remainder is molybdenum powder, wherein the total mass percentage of the content of each component of the raw material powder is 100%, and the raw material powders with the proportions are mixed and ball-milled, wherein the ball milling is performed by mixing the powders in a ball mill for 60 hours to obtain a mixed molybdenum alloy powder;

[0032] (2) placing the molybdenum alloy powder obtained in step (1) into a circular graphite mold with a diameter of 30 mm, and covering the outside of the graphite mold with graphite felt to prevent heat loss;

[0033] (3) placing the graphite mold containing molybdenum alloy powder in step (2) into the SPS furnace chamber, starting the hydraulic system, manually controlling the pressure head to descend, and pre-loading the mold, wherein the pre-loading pressure is 10 MPa and the time is 15 s;

[0034] (4) Align the center of the graphite mold after pre-loading in step (3) with the infrared temperature measuring hole of the SPS sintering furnace, close the furnace door, apply a pressure of 40 MPa to the graphite mold, and evacuate the furnace chamber to 10 -2Pa, and then sintering is carried out. The sintering process is specifically as follows: first, the temperature is heated from room temperature to 600°C within 5 minutes; secondly, it is heated from 600°C to 1700°C at a heating rate of 100°C / min, and finally it is heated from 1700°C to 1800°C at a heating rate of 50°C / min, and is kept at 1800°C for 20 minutes. After the insulation is completed, it is naturally cooled to 40°C to obtain a molybdenum alloy.

[0035] The microstructure scanning electron microscope photos of the molybdenum alloy samples are shown in Figure 1 As shown in the middle figure (b), it can be seen that the alloy sample has uniform structure, fine grains and no obvious pores.

[0036] After testing, the hardness of the molybdenum alloy sample is 453.1HV and the density is 98.25%.

[0037] Embodiment 3:

[0038] (1) Mo, TiH2, ZrH2, C, and Cr powders are used as raw materials, and the content of each component in the raw materials is calculated by mass percentage as follows: TiH2: 0.4%, ZrH2: 0.08%, C: 0.06%, Cr: 12%, and the remainder is molybdenum powder, wherein the total mass percentage of the content of each component of the raw material powder is 100%, and the raw material powders with the proportions are mixed and ball-milled, wherein the ball milling is performed by mixing the powders in a ball mill for 60 hours to obtain a mixed molybdenum alloy powder;

[0039] (2) placing the molybdenum alloy powder obtained in step (1) into a circular graphite mold with a diameter of 30 mm, and covering the outside of the graphite mold with graphite felt to prevent heat loss;

[0040] (3) placing the graphite mold containing molybdenum alloy powder in step (2) into the SPS furnace chamber, starting the hydraulic system, manually controlling the pressure head to descend, and pre-loading the mold, wherein the pre-loading pressure is 10 MPa and the time is 15 s;

[0041] (4) Align the center of the graphite mold after pre-loading in step (3) with the infrared temperature measuring hole of the SPS sintering furnace, close the furnace door, apply a pressure of 40 MPa to the graphite mold, and evacuate the furnace chamber to 10 -2 Pa, and then sintering is carried out. The sintering process is specifically as follows: first, the temperature is heated from room temperature to 600°C within 5 minutes; secondly, it is heated from 600°C to 1700°C at a heating rate of 100°C / min, and finally it is heated from 1700°C to 1800°C at a heating rate of 50°C / min, and is kept at 1800°C for 20 minutes. After the insulation is completed, it is naturally cooled to 40°C to obtain a molybdenum alloy.

[0042] The microstructure scanning electron microscope photos of the molybdenum alloy samples are shown in Figure 1As shown in the middle figure (c), it can be seen that the alloy sample has uniform structure, fine grains and no obvious pores.

[0043] After testing, the hardness of the molybdenum alloy sample is 557.2HV and the density is 98.21%.

[0044] Comparative Example 1:

[0045] The technical solution of Example 1 disclosed in the Chinese patent with application number 202111480498.2 and invention name “A preparation method of WC particle reinforced Mo-based alloy and its product” is used as Comparative Example 1 of the present invention;

[0046] That is, in comparative example 1, the amount of tungsten carbide added is 12% by mass, and the remainder is molybdenum powder. The mixing is carried out in a drum mill, the powder is assembled with a mixing bottle, the ball-to-material ratio is 4:1, and then the powder is mixed at a speed of 120r / min for 24h to obtain a mixed material.

[0047] The mixed material is placed in a mold and pressed by an electronic universal testing machine at a pressing pressure of 200 MPa to obtain a compact.

[0048] The compact is placed in a high-temperature sintering furnace for sintering, and the sintering atmosphere is hydrogen. The sintering process is to first increase the temperature to 1000°C at a rate of 15°C / min, and when the temperature is higher than 1000°C, the heating rate is 10°C / min, and the temperature is kept at 1100°C for 2 hours, and at 1900°C for 4 hours, and then the temperature is reduced to 500°C at a rate of 10°C / min, and finally cooled with the furnace; a WC particle reinforced Mo-based alloy is obtained.

[0049] The hardness of the WC particle reinforced Mo-based alloy is 242.74 HV.

[0050] Comparative Example 2:

[0051] The technical solution of Example 2 disclosed in the Chinese patent with application number 202211034158.1 and invention name “A high-hardness TZM alloy and preparation method thereof” is used as Comparative Example 2 of the present invention;

[0052] That is, in Comparative Example 2, (1) Mo powder, TiH2 powder, ZrH2 powder, TiB2 powder, ZrB2 powder and C powder are selected as raw materials of TZM alloy, the Fischer-Weiss particle size of Mo powder is 3.4 μm, and the Fischer-Weiss particle size of the remaining powders is 1.8 μm; calculated by mass percentage, TiH2: 0.25%, ZrH2: 0.02%, TiB2: 0.3%, ZrB2: 0.07%, C: 0.03%, and the remainder is Mo; wherein, Mo powder is sieved through a 160-mesh sieve, and the other powders are sieved through a 270-mesh sieve for later use;

[0053] (2) taking the TiH2 powder, ZrH2 powder, TiB2 powder, ZrB2 powder and C powder obtained in step (1), firstly disperse and mix them with 20% Mo powder through a 160-mesh sieve, and then place them in a vacuum mixer with the remaining Mo powder and stir them uniformly to obtain a mixed powder;

[0054] (3) The mixed powder of step (2) is loaded into a 120×260×800 mm flexible mold, and is pressed into a powder blank by cold isostatic pressing at 240 MPa for 20 min, and then set aside;

[0055] (4) The powdery blank was placed in a sintering furnace and sintered at 1900°C in a hydrogen environment for 44 hours. The density obtained by sintering was 9.84 g / cm 3 The sintered blank is obtained; during the heating process, the temperature is kept at 700°C for 2 hours and at 1000°C for 4 hours;

[0056] (5) heating the sintered billet at a temperature of 1250° C. for 90 min, and rolling the billet. The single rolling deformation is 16% and the total rolling deformation is 74%, thereby obtaining a rolled TZM billet for standby use.

[0057] (6) annealing the rolled TZM slab in step (5) at a temperature of 850° C. for 1.5 h to completely remove the processing stress, and then cooling for standby use;

[0058] (7) machining the blank processed in step (6) to a target required size, and then performing defect detection;

[0059] (8) The product that has passed the nondestructive test in step (7) is rinsed with clean water, dried, and vacuum packaged to obtain a finished product. The hardness of the finished product is tested by a Vickers hardness tester, and the hardness is 280 HV.

[0060] The hardness comparison of the alloys prepared in Examples 1-3 and Comparative Examples 1-2 is shown in Table 1.

[0061] Table 1. Comparison of hardness of high hardness molybdenum alloys prepared in Examples 1-3 and alloys prepared in Comparative Examples 1-2

[0062]

[0063]

[0064] The Cr contents in Examples 1-3 are 6.0%, 9.0%, and 12%, respectively. As can be seen from Table 1, the hardness of the alloy increases significantly with the increase of the Cr content in the examples; when the Cr content is 12% (ie, Example 3), the hardness of the molybdenum alloy reaches the maximum, which is 557.2HV. Compared with the TZM alloy prepared in Comparative Example 2, the hardness is about twice that of the TZM alloy, and compared with the WC particle reinforced Mo-based alloy prepared in Comparative Example 1, the hardness is increased by more than 1 times. The molybdenum alloy prepared with the lowest Cr content (ie, Example 1) is better than Comparative Examples 1 and 2 in terms of hardness. It can also be seen from Table 1 that the density of the molybdenum alloys prepared in Examples 1-3 is above 98%, and the density increases slightly with the increase of chromium content.

[0065] The above is only an embodiment of the present invention, and does not limit the present invention in any form. The present invention can also have other forms of embodiments according to the above structures and functions, which are not listed one by one. Therefore, any simple modification, equivalent change and modification made by any technician familiar with the profession to the above embodiment according to the technical essence of the present invention without departing from the scope of the technical solution of the present invention still falls within the scope of the technical solution of the present invention.

Claims

1. A method for preparing a high hardness molybdenum alloy, characterized in that: The specific steps include: (1) using Mo, TiH2, ZrH2, C and Cr powders as raw materials, mixing and ball milling according to a certain ratio to obtain a uniformly mixed molybdenum alloy powder; (2) placing the molybdenum alloy powder obtained in step (1) into a graphite mold, and covering the outside of the graphite mold with graphite felt; (3) placing the graphite mold containing molybdenum alloy powder in step (2) into the SPS furnace chamber and pre-loading the mold; (4) The blank obtained after pre-pressing and loading in step (3) is placed in an SPS sintering furnace for sintering, and a high-hardness molybdenum alloy is obtained after the sintering is completed.

2. The method for preparing a high hardness molybdenum alloy according to claim 1, characterized in that: The ball milling in step (1) is performed by mixing the powders in a planetary ball mill for 60 hours.

3. The method for preparing a high hardness molybdenum alloy according to claim 1, characterized in that: The content of each component in the raw material in step (1) is calculated as follows in mass percentage: Cr powder: 6-12%, TiH2 powder: 0.4-0.6%, ZrH2 powder: 0.08-0.1%, C powder: 0.06-0.07%, and the remainder is molybdenum powder, wherein the total mass percentage of the content of each component of the raw material powder is 100%.

4. The method for preparing a high hardness molybdenum alloy according to claim 1, characterized in that: In step (2), the graphite mold is a circular graphite mold with a diameter of 30 mm.

5. The method for preparing a high hardness molybdenum alloy according to claim 1, characterized in that: In step (3), the graphite mold loaded with molybdenum alloy powder in step (2) is placed in the SPS furnace chamber, the hydraulic system is started, the pressure head is manually controlled to descend, and the mold is pre-loaded, the pre-loading pressure is 10Mpa, and the time is 10-20s.

6. The method for preparing a high hardness molybdenum alloy according to claim 1, characterized in that: In step (4), the center of the graphite mold after pre-compression loading in step (3) is aligned with the infrared temperature measuring hole of the SPS sintering furnace, the furnace door is closed, a pressure of 40 MPa is applied to the graphite mold, and the furnace chamber is evacuated to 10 -2 Pa, and then sintering.

7. The method for preparing a high hardness molybdenum alloy according to claim 6, characterized in that: In step (4), the sintering process is specifically as follows: first, heating the temperature from room temperature to 600°C within 5 minutes; secondly, heating from 600°C to 1700°C at a heating rate of 100°C / min, and finally heating from 1700°C to 1800°C at a heating rate of 50°C / min, and keeping at 1800°C for 20 minutes. After the insulation is completed, naturally cooling to 40°C to obtain a molybdenum alloy.

8. The molybdenum alloy obtained by the preparation method according to any one of claims 1 to 7.

9. The molybdenum alloy according to claim 8, characterized in that The molybdenum alloy has a hardness of 409.4HV-557.2HV and a density of more than 98.06%.

Citation Information

Patent Citations

  • A method for preparing WC particle-reinforced Mo-based alloys and its products

    CN114134386B

  • High-hardness TZM alloy and preparation method thereof

    CN115612904A

  • Sintered titanium-based decorative article - has inorganic cpds. in titanium matrix derived from titanium hydride

    CH687622A5

  • Manufacture method of molybdenum alloy for nuclear fusion device

    CN102796929A

  • Preparation method of high-performance powder metallurgy TZM alloy

    CN109371274A